Transcriptomic Profile and Probiotic Properties of Lactiplantibacillus pentosus Pre-adapted to Edible Oils - Alonso García, Esther; de la Fuente Ordoñez, Juan José; Lavilla Lerma, Leyre; Estudillo-Martínez, María D.; Castillo-Gutiérrez, Sonia; Benomar, Nabil; Knapp, Charles W.; Abriouel, Hikmate (Frontiers in Microbiology, 2021)
In this study, we determined whether pre-adapting Lactiplantibacillus pentosus strains, isolated from Aloreña green table olives, to vegetable-based edible oils improved their robustness and functionality; this may have great importance on their stress response during fermentation, storage and digestion. Pre-adapting the strains to the corresponding oils significantly increased their probiotic functionality (e.g., auto-aggregation, co-aggregation with pathogens, and mucin adhesion), although results depended on the strain and the oil used for pre-adaptation. As such, we selected olive-adapted L. pentosus AP2-16, which exhibited improved functionality, and subjected it to transcriptomic profiling with the aim to understand the molecular mechanisms involved in the adaptation and the increased functionality. Global transcriptomic analysis of oil-adapted (olive or almond) and non-adapted (control) L. pentosus AP2-16 realized that 3259 genes were expressed, with 2779 mapped to the reference database. Comparative transcriptomic analysis showed that 125 genes (olive versus control) and 108 genes (olive versus almond) became significantly differentially expressed. Olive-adapted L. pentosus AP2-16 responded by rerouting its metabolic pathways to balance energy production and storage, cell growth and survivability, host interactions (glycoconjugates), and other physiological features. As such, the pre-adaptation of lactobacilli with olive oil switches their transcriptional network to regulate robustness and functionality, possibly representing a novel approach towards the design and manufacture of probiotic products with improved stability and functionality.